The use of classpoint for student engagement in learning computer and information processing - Md Enzai, Nur Idawati; Che Kar, Siti Aishah; Ahmad, Norhayati; Rais, Siti Sara (2025)
Computer and Information Processing is a servicing type of subject for Diploma in Office Management and Technology students. This subject involves two hours of lecture and two hours of laboratory per week. Nine chapters need to be covered during the lecture within 14 weeks. All the chapters involve lots of theoretical concepts and terms that are quite dry compared to the laboratory session. It is challenging to ensure engagement and participation of students in class, especially for Generation Z, who are known to have very short attention span. Therefore, ClassPoint platform is used to make the class livelier and more exciting during the teaching and learning process. ClassPoint is a learning platform that can be integrated with PowerPoint, with various interactive activities. Among the attractive features of ClassPoint is the accumulation of stars awarded by the instructor according to their participation or achievement. Through observation by instructors, the students would pay more attention when ClassPoint activity is conducted and are eager to get involved compared to conventional lectures. The students’ perceptions are obtained through a questionnaire survey, and the findings are analyzed for future action and improvement